Role of nitric oxide in the remodelling of extracellular matrix in myxomatous mitral valve degeneration of dogs and pigs - dos Corrêa, Leonardo R.; Faleiro, Mariana B. R.; Rodrigues, Marcela M. P.; Amaral, Hidelbrando R. D.; Filho, José B. Gama; Matos, Moema P. C.; Amorim, Renée Laufer [UNESP]; de Moura, Veridiana M. B. D. (My University, 2011)
Myxomatous mitral valve degeneration (MMVD) or endocardiosis is a heart valve disease that occurs in many mammalian species, especially in humans, dogs and pigs. Nitric oxide (NO) plays an important role in the MMVD development. NO can be indirectly evaluated by the nitric-oxide synthase (NOS) expression and by the histochemical reaction of nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d). The aim of this study was to evaluate NOS activity, by NADPH-d reaction, in the anterior leaflet of dogs with regular mitral valves and in those with MMVD, as well as in young swine and old females, comparing the reaction level with the degree of endocardiosis disease and also the histological alterations. Twelve mitral valves of dogs and 22 of swine were used for the research. All the valves were macroscopically analyzed for the occurrence or not of endocardiosis. They were fixed in a 4% paraformaldehyde, exposed to NADPH-d reaction, routinely processed and microscopically evaluated for the detection of mucopolysaccharides (MPS) deposition, collagen degeneration, fibrosis and level of endocardiosis. In dogs, relation was observed between higher intensity of the NADPH-d reaction, higher endocardiosis degree, MPS deposition as well as the collagen degeneration. No alteration in color was observed in pigs ́ valves during NADPH-d reaction. In conclusion, NO works in canine mitral valve remodeling extracellular matrix and plays an important role in endocardiosis disease. In swine, the lack of reaction reinforces the absence of macroscopical endocardiosis lesions, suggesting restrict NO action or major differences in the structures of swine valves.
Keywords: Dog; Endocardiosis; NADPH; NOS; Swine; Valve